Framework proposal for Role-Playing Games as mental health intervention: the Critical Skills methodology - Otani, Victor Henrique Oyamada; Novaes, Rafael A. C. B.; Pedron, Julia; Nabhan, Pedro Chen; Rodrigues, Thaísa Malbar; Chiba, Ryo; Guedes, João Vitor Cardoso; Marques, Lucas Murrins; Vissoci, João Ricardo Nickenig (Frontiers in Psychiatry, 2024)
Gamified interventions are an emerging approach in mental health treatment and prevention. Their positive effects on managing various clinical conditions stem from enhancing social skills. However, cost-effective options like Table-top Role-Playing Games (TTRPGs), which offer similar benefits to other game-based interventions, lack standardized methods for ensuring replicability. In this regard, the method outlined in this study endeavors, in a structured and guided manner drawing from the Consolidated Framework for Implementation Research (CFIR), to establish a six-step protocol for developing an intervention method utilizing TTRPGs. In all Steps, we aim to anchor ourselves in robust literature concerning social skills training (SST), cognitive behavioral therapy (CBT), and gamification comprehensively. Thus, the method presented encompasses the objectives of SST, the strategies of CBT, and the dynamics of gamification via TTRPGs. Furthermore, we demonstrate a possible application of the method to illustrate its feasibility. Ultimately, the final method is structured, evidence-based, easily applicable, cost-effective, and thus viable. Mental health professionals seeking a structured and instructional tool for protocol development will find support in the method proposed here.